Poverty and development into the 21st century - Allen, Tim (Ed.); Thomas, Alan (Ed.) (Oxford Oxford University Press, 2000)
This is a revised edition of an ambitious book. The original book aimed to introduce poverty and development in the 1990s The Cold war has receded into history and it has become clear that our previous concentration on development as a post World-War phen
Keywords: Poverty; Economic development projects; Industrialization